Design and data analysis of wearable sports posture measurement system based on Internet of Things - Yanmin Zhao; Yang You (Alexandria Engineering Journal, 2021)
Aiming at sports and daily training of athletes in rehabilitation therapy, a wearable sports posture measurement system is proposed in combination with the Internet of Things technology. By choosing a professional coach to wear the system, the experiment was verified with common sports postures, and the actual measured sports information was analysed and processed. The experimental results show that the system can perform stable online monitoring of the exercise process, and the data analysis results have a certain reference value for the evaluation of the patient's physical condition during rehabilitation and the daily training evaluation of athletes.